1992
DOI: 10.1002/star.19920440905
|View full text |Cite
|
Sign up to set email alerts
|

Extrudates of Cornstarch with Urea and Glycols: Structure/Mechanical Property Relations

Abstract: Urea, various glycols and mixtures of these were tested as plasticizers for gelatinized cornstarch. Mixtures of cornstarch, urea andor triethylene glycol, glycerol or propylene glycol were extruded into ribbons. Mechanical and structural properties of the ribbons were evaluated by tensile testing, DSC and NMR. Flexible ribbons were obtained only when enough urea or glycol was present to lower the glass transition temperature of the starch near or below room temperature. Ribbons containing high levels of urea w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(44 citation statements)
references
References 10 publications
3
41
0
Order By: Relevance
“…26 Several articles have Compression Molding been published on the mechanical properties of TPS and extruded starches prepared from several starch Starches were mixed with a constant amount of sources, such as maize, wheat, potato, waxy maize, glycerol to give the following composition: starch : and amylomaize starch. [27][28][29][30][31][32][33][34][35] It has been shown that glycerol Å 100 : 30 (w/w on the basis of dry the amount of amylose and amylopectin affects the starch). These premixes were further mixed with crystallinity present in glycerol-containing TPS water to obtain mixtures with water contents in plastics, but no relationships with properties have the range of 8-35% (w/w on the basis of total been reported.…”
Section: Methodsmentioning
confidence: 99%
“…26 Several articles have Compression Molding been published on the mechanical properties of TPS and extruded starches prepared from several starch Starches were mixed with a constant amount of sources, such as maize, wheat, potato, waxy maize, glycerol to give the following composition: starch : and amylomaize starch. [27][28][29][30][31][32][33][34][35] It has been shown that glycerol Å 100 : 30 (w/w on the basis of dry the amount of amylose and amylopectin affects the starch). These premixes were further mixed with crystallinity present in glycerol-containing TPS water to obtain mixtures with water contents in plastics, but no relationships with properties have the range of 8-35% (w/w on the basis of total been reported.…”
Section: Methodsmentioning
confidence: 99%
“…The is sometimes mentioned in the literature 15 but ducted exactly 48 h after their preparation. However, as the casting method is not reproducible, calorimetric measurement procedure was similar the glycerol contents of films specially prepared for all samples regardless of composition.…”
Section: Introductionmentioning
confidence: 99%
“…But even in this case, the mechanical properties of the materials produced are very poor (especially in tensile strength), depending on the kind of plasticizer used. 7 Glycerol is the most effective plasticizer but still cannot prevent the degradation of starch macromolecules during plasticization. It was found that the decomposition depends on the amount of glycerol as well as on the temperature used.…”
Section: Introductionmentioning
confidence: 99%